A comparison of COPD patients with and without ACOS in the ECLIPSE study. Issue 5 (17th March 2016) - Wurst, Keele E.; Rheault, Tara R.; Edwards, Lisa; Tal-Singer, Ruth; Agusti, Alvar; Vestbo, Jørgen
There is growing interest in asthma–chronic obstructive pulmonary disease (COPD) overlap syndrome (ACOS) [1, 2]. Yet, there is no consensus on the best definition of ACOS [1, 2] and, therefore, it is difficult to appropriately characterise these patients. Here, we compare the main clinical characteristics and outcomes of COPD patients with and without ACOS in the ECLIPSE cohort [3] according to six different definitions of ACOS. ECLIPSE offers an opportunity to examine ACOS in a large well-characterised COPD cohort followed over 3 years  http://ow.ly/Zcycr